Platinum Vacation Rentals - Jones, Cameron (My University, 2022)
I choose to create my honors project simultaneously with the business I started while in college. My business is called Platinum Vacation Rentals and I am a property manager at the Lake of the Ozarks. I currently manage seven rental properties for my clients. Throughout this project I will explain the steps I took to get to where I am today, the materials I have created and maintained, as well as how Covid impacted my business and my future plans for Platinum Vacation Rentals.